Այգու հողամշակ ֆրեզ-մեքենայի արտաշարժ բանող օրգանի շարժաթևիշարժահաղորդ մեխանիզմի կինեմատիկական վերլուծությունը - Պապյան, Սերյոժա; Հարությունյան, Գևորգ (ՀԱԱՀ հիմնադրամ)
Произведены кинематический анализ приводного механизма кривошипа почвообрабатывающей фрезмашины для межствольного и приствольного пространства садов и оценка качества ее работы. Разработаны соответствующие расчетные схемы и выявлены закономерности изменения траектории движения вращающегося центра фрезы и коэффициента оценки качества работы фрезмашины в зависимости от суммарной величины радиуса ствола и ширины защитной зоны. Установлено, что при минимальном значении rծ+b (70 мм) площадь необработанного приствольного пространства сокращается на 83,7 %, а продолжительность цикла обхода стволов деревьев – в 1,58 раза, в результате увеличивается обработанная площадь межствольного пространства This study presents a kinematic analysis of the crankdriven mechanism powering the movable working body of a garden milling machine used for intertrunk and neartrunk soil cultivation. The aim is to enhance the quality of intertrunk tillage by minimizing the unprocessed area between the tillage cutter and the protected zone around tree trunks. The object of the study is a garden milling machine developed at the Scientific Department of Livestock and Fodder Production Mechanization, Research Institute of the Armenian National Agrarian University. The machine›s control system enables the hydraulic cylinder piston to be fixed not only at the end positions but also at intermediate points while maneuvering around tree trunks. A kinematic diagram of the mechanism was developed, and the trajectories of the cutter’s center of rotation were determined for both full and partial piston strokes. Relevant calculation formulas were derived, and the variations in unprocessed areas were analyzed in both scenarios. Additionally, the work efficiency coefficient (K) was calculated based on the combined radius of the tree trunk and its protective zone (rծ + b). The analysis revealed that fixing the piston in intermediate positions significantly reduces the unprocessed area compared to using the full piston stroke. Furthermore, as the combined value of (rծ + b) decreases, the efficiency coefficient K increases, reaching a maximum of 83.7 % at a minimum value of (rծ + b) = 7 cm․
Keywords: Ագրարային ճարտարագիտություն